EID STUDY EVENT: STOCK PRICES AND STOCK TRADING VOLUME BEFORE AND AFTER EID 2024 IN THE ENERGY SECTOR - Andhika, Bambang Mahendra; Suryaningsum, Sri; Fikri Dwi Prasetya (Count : Journal of Accounting, Business and Management, 2024)
This paper presents the results of the analysis of the Eid study event that affects stock prices and stock trading volumes before and after Eid in 2024 in the energy sector. The analysis was carried out by testing the difference in stock prices and differences in stock trading volumes before Eid compared to after Eid. The energy sector was chosen because it is a sector that is closely related to Eid, where during Eid, energy production in Indonesia is usually not as much as other days. The analysis tool used is compare mean paired differences because the research was conducted to test the Eid event with differences before and after Eid. This study uses a sample of ten energy companies consisting of coal mining companies, oil and gas companies, and energy facility support companies with 5 daily data points before and 5 days after Eid so that the total data is 50 stock price data and 50 stock trading data. The result is that the average mean of stocks and stock trading volume before Eid is lower than the mean after Eid. For the results of statistical data testing, the results are statistically that the stock prices before and after Eid are not different, although the mean stock price before Eid is lower when compared to the mean stock price after Eid. For the results of statistical testing of the stock trading volume variable, there is a significant difference; in this case, the trading volume before Eid is lower than the trading volume after Eid. This means that the 2024 Eid event has a real effect on changes in stock trading volume before and after Eid 2024. This study is useful for investors if they invest before Eid, especially in the energy sector during Eid 2024.